TYPHOID PERFORATIONS - PROGNOSTIC FACTORS AND MODE OF TREATMENT - Sultan, Syed; Ahmed, Rashid; Afridi, Shah Jehan; Qureshi, Zahir; Khattak, Irfan -ud-Din (Journal of Ayub Medical College Abbottabad, 1992)
ABSTRACT: This report examines the characteristics of 60 patients with typhoid perforations, treated over a period of 7.5 years, ending September, 1990. The most important prognostic determinants were perforation/operation interval, age of the patient and mode of treatment. 15% cases were treated conservatively with 11.11% mortality, in 3% only a drainage procedure could be instituted with a 50% mortality and definitive treatment in the form of simple closure (in 54% cases), and wedge resection (in 28% cases) yielded 22.5% and 18% mortality respectively.